Bond Graph Modelling and Simulation of Walking Mechanism of Quadruple Robot - Soharu, Garima (My University, 2017)
Legged robots have capability of traversing any type of terrain with much ease and stability compared to wheeled robots. The uniqueness of legged robots are that they don’t have continuous contact with ground thus helping them select their footsteps to avoid obstacles. Other advantageous properties of legged robots are that they cause less damage to the terrain, their ability to bend on the joints give the property of active suspension, and they can walk in every direction, which gives them leverage to navigate through crowded and compact surroundings. The objective of this thesis is to model and simulate a walking mechanism for quadruple model which is stable and is able to implement different types of gaits. The stability control of legged robot is of utmost importance as compared to wheeled robot as contact from ground is discontinuous due to lifting and placing of leg. The positing of legs relative to body of robot considerably effects the stability, also the sequence and timing in which legs are moved and placed play important role in energy efficiency. Here three models for walking mechanism has been developed using bond graph technique. First the mechanism for two legs is modelled, further two different models for walking of quadruple have been developed. Results from simulation are discussed. The comparison of different gaits are done for energy efficiency.
Master of Engineering -CAD/CAM
Keywords: Locomotion; Gaits; Bond graph modelling; Planar model; Quadruple; Stability